Assessing the Anxiolytic and Relaxation Effects of Cinnamomum camphora Essential Oil in University Students: A Comparative Study of EEG, Physiological Measures, and Psychological Responses - Gong, Xiangfei; Yang, Yujun; Xu, Tong; Yao, Dongsheng; Lin, Shengyu; Chang, Weiyin (Frontiers in Psychology, 2024)
Background Cinnamomum camphora is a commercially important tree species in China, and it’s also a common native tree in the forests of southern China. However, literature on the impact of Cinnamomum camphora essential oil (CCEO) on human psychophysiological activity is scarce. Hence, the primary objective of this study was to examine the effect of exposure to CCEO on the functioning of the human autonomic nervous system, electroencephalographic (EEG) activity, and emotional state. Methods Forty-three healthy university students participated. The data collected included heart rate (HR), blood pressure (BP), pulse rate, blood oxygen saturation (SpO2), electroencephalographic (EEG) activity, and the results of the Profile of Mood States (POMS) test. Results A drop in diastolic pressure (DBP) and pulse rate was also noticed after participants inhaled CCEO. Furthermore, EEG studies have demonstrated notable reductions in absolute beta (AB), absolute gamma (AG), absolute high beta (AHB), and relative gamma (RG) power spectra during exposure to CCEO. Conversely, the relative theta (RT) and power spectra values showed a significant increase. Additionally, the finding from POMS indicated that the fragrance evoked positive emotions and suppressed negative feelings. Conclusion The results suggest that exposure to CCEO may promote mental and physical relaxation, facilitate cognitive processes such as memory and attention, and enhance mood states.